A study on bioecology of macroalgae, genus Caulerpa in northern Minahasa Waters, North Sulawesi Province - Pulukadan, Irma; Keppel, Rene Ch; Gerung, Grevo S (AQUATIC SCIENCE & MANAGEMENT, 2013)
Alga is a marine resource of potential to fisheries and marine sector. It has an important economic value to promote the economy in Indonesia. Nowdays, algae have been used as a relatively high value fisheries commodity since it has been used for food, industrial, pharmaceutical and cosmetic raw materials. This important potential needs to be supported with understanding of its biology and ecology, so that its utilization could increase the livelihood of the coastal villagers. This study was aimed at inventorying and identifying the members of genus Caulerpa found in North Minahasa Regency waters and studying some biological and ecological aspects of the algae in the area. Resuls showed that there were 7 species recorded, Caulerpa racemosa, C. racemosa var. macrophysa, C. sertularioides, C. taxifolia, C. serrulata,C. lentillifera and C. peltata. Ecologically, the environmental parameters, such as water temperature, salinity, pH, dissolved oxygen, turbidity, were in tolerable ranges for algal growth. Bottom substrate supported the growth of genus Caulerpa as well© Saat ini alga dijadikan sebagai komoditas hasil perikanan dengan nilai ekonomis yang relatif tinggi karena manfaatnya sebagai bahan makanan serta bahan baku industri, farmasi, dan kosmetik. Potensi yang cukup penting ini harus ditunjang dengan ilmu pengetahuan tentang biologi dan ekologi dari alga laut, sehingga pemanfaatannya dapat meningkatkan taraf hidup masyarakat pesisir. Penelitian tentang kajian bioekologi alga makro genus Caulerpa di perairan Minahasa Utara ini dilaksanakan dan diharapkan dapat memberikan informasi ilmiah tentang bioekologi alga makro genus Caulerpa, sehingga dapat dimanfaatkan untuk pengembangan pemanfaatan bagi kepentingan masyarakat pesisir khususnya dan industri alga makro umumnya. Penelitian ini bertujuan untuk menginventarisasi dan mengidentifikasi alga makro genus Caulerpa di perairan Kabupaten Minahasa Utara, dan mengkaji aspek bioekologinya. Hasil penelitian menunjukkan bahwa ditemukan 7 spesies, yaitu Caulerpa racemosa, C. racemosa var. macrophysa, C. sertularioides, C. taxifolia, C. serrulata, C. lentillifera dan C. peltata. Parameter lingkungan seperti suhu, salinitas, pH, oksigen terlarut, tingkat kecerahan air berada pada kisaran yang dapat ditolerir untuk pertumbuhan alga makro, sedangkan substrat juga mendukung pertumbuhan alga makro ini©